Combined treatment: impact of optimal psychotherapy and medication in bipolar disorder. (21st July 2014) - Parikh, Sagar V; Hawke, Lisa D; Velyvis, Vytas; Zaretsky, Ari; Beaulieu, Serge; Patelis‐Siotis, Irene; MacQueen, Glenda; Young, L Trevor; Yatham, Lakshmi N; Cervantes, Pablo
<x xml:space="preserve">Abstract</x> Objectives The current study investigated the longitudinal course of symptoms in bipolar disorder among individuals receiving optimal treatment combining pharmacotherapy and psychotherapy, as well as predictors of the course of illness. Methods A total of 160 participants with bipolar disorder (bipolar I disorder: n = 115; bipolar II disorder: n = 45) received regular pharmacological treatment, complemented by a manualized, evidence‐based psychosocial treatment – that is, cognitive behavioral therapy or psychoeducation. Participants were assessed at baseline and prospectively for 72 weeks using the Longitudinal Interval Follow‐up Evaluation (LIFE) scale scores for mania/hypomania and depression, as well as comparison measures (clinicaltrials.gov identifier: NCT00188838). Results Over a 72‐week period, patients spent a clear majority (about 65%) of time euthymic. Symptoms were experienced more than 50% of the time by only a quarter of the sample. Depressive symptoms strongly dominated over (hypo)manic symptoms, while subsyndromal symptoms were more common than full diagnosable episodes for both polarities. Mixed symptoms were rare, but present for a minority of participants. Individuals experienced approximately six significant mood changes per year, with a full relapse on average every 7.5 months. Participants who had fewer depressive symptoms at intake, a later age at onset, and no history of psychotic symptoms spent more weeks well over the course of the study. Conclusions Combined pharmacological and adjunctive psychosocial treatments appeared to provide an improved course of illness compared to the results of previous studies. Efforts to further improve the course of illness beyond that provided by current optimal treatment regimens will require a substantial focus on both subsyndromal and syndromal depressive symptoms.